The Audit of Control System With Information Technology - Gunawan, Henry; Amin, Muhd Nuryatno (Fundamental Management Journal, 2018)
This article speaks about the internal control system using the help of computer applications.The purpose of this article is to inform a shift of use in the control and supervision of operational system procedures in a previously manual with input or copy and paste from a data source to a particular software, but now from existing software applications can directly retrieve from data sources. This article presents the framework of information technology and research method for auditing in relation to quality control systems in IT domains. Limitations of this study on data, time and cost, as well as methods of statistical research with different test. The strength of this research gives inspiration and ideas in auditing that currently having issues disruption. For next research can focus on respondents from public accounting firms or financial institutions by multivariate statistic with some independent variables that influence internal control.Keyword: system informasi, tecnologi informasi, manajemen perusahaan, system audit